Theodosius Dobzhansky e o desenvolvimento da genética de populações de Drosophila no Brasil: 1943-1960 - Sião, José Franco Monte (2008)
The Ukrainian geneticist Theodosius Dobzhansky (1900-1975) made several visits to Brazil and for four times interacted with the group leaded by Prof. André Dreyfus (1897-1952), of the University of São Paulo. The partnership between Dobzhansky and Brazilian researchers was marked by the development of a project which lasted about twenty years and was supported by the Rockfeller Foundation. The first aim of this dissertation is to evaluate the impact made by Dobzhansky s four visits on the studies of genetics and evolution developed by the Brazilian group. The second aim is to analyse the scientific and extra-scientific factors which lead to the decrease of Brazilian and Dobzhansky s publications related to the subject of the project as well as the end of their partnership. The period considered is from 1943 to 1960. This dissertation contains an introduction and five chapters. The first chapter presents a general view of the scientific context of the period, an overview of Dobzhansky s career and of genetics in Brazil. The second chapter tries to analyse the impact made by Dobzhansky s visits on the studies developed by Dreyfus group using a bibliometric approach. The third chapter deals with the subjects discussed by Dreyfu s group during and after Dobzhansky s visits, studying a significant sample of their works. The fourth chapter tries to elucidate the scientific and extra-scientific factors which contributed to the decrease of Dobzhansky and Brazilians publications related to the subject of the project. The fifth chapter presents some final considerations. This study lead to the conclusion that Dobzhanky s influence on Dreyfus group was significant not only in quantitative terms (the amount of publications beginning with Dobzhansky s first visit), but also in qualitative terms. After Dobzhansky s arrival, Dreyfus group started a new line of investigation (the genetics of populations) adopting a new experimental material (Drosophila) and exploring a little studied region: the tropical one. The decrease of individual and joint publications dealing with the subject of the project during some periods can be explained by the adoption of new experimental materials by some members of the group; the involvement with some subjects which were not part of the initial project, such as Botany; Dobzhansky and his wife s health problems during the third visit; scientific disagreement between Dobzhansky and Brazilians; and Brazilian s desire of independence